“Estudio de la gastronomía típica y de la cultura de las huecas y recetas culinarias de la zona centro de la provincia de los Ríos - 2020”. - Darlene Elizabeth Barre Intriago (2020)
This research project covers the study of the central zone of the province of Los Ríos in the cantons of Mocache, Quinsaloma, Palenque, Vinces and Ventanas with the purpose of creating a gastronomic guide with the most representative recipes of each canton. The general objective of the research project was to analyze the typical gastronomy, hollows and recipes of the cantons of the central zone of the province, where three objectives were established, the first is aimed at the diagnosis of the current situation of gastronomy, hollows and recipes of each canton, through surveys conducted to each of the owners of the hollows information was obtained on the typical gastronomy, in the second objective information was compiled for the technical data sheets of the recipes and hollows where general data of the recipes and each establishment from its beginnings to the present was acquired. Subsequently, in the last objective, a gastronomic guide of recipes and hollows of each of the mentioned cantons was elaborated with data such as the name of the hollow, owner, address, photo and description of the typical dish, brief history of the hollow and the typical recipes of each canton, with the purpose of informing the inhabitants of the place and visitors about the gastronomy of each place. Keywords: typical gastronomy, culinary hollows, recipes, gastronomic guide